Novel substituted aminothiazoles as potent and selective anti-hepatocellular carcinoma agents. Issue 23 (1st December 2016) - Lu, Huagang; Rogowskyj, John; Yu, Wenquan; Venkatesh, Anu; Khan, Noshena; Nakagawa, Shigeki; Goossens, Nicolas; Koh, Anna P.; Higashi, Takaaki; Gunasekaran, Ganesh; Schwarz, Myron E.; Hiotis, Spiros P.; et al.
Graphical abstract: Abstract: Based on our previous identification of a disubstituted aminothiazole termed HBF-0079 with promising selective toxicity for HCC-derived cell lines versus non-HCC liver lines, a series of tri-substituted aminothiazole derivatives were prepared and evaluated. This work resulted in the discovery of isopropyl 4-(pyrazin-2-yl)-2-(pyrimidin-2-ylamino)thiazole-5-carboxylate, 14, which displayed EC50 value of 0.11 μM and more than 450 times of selectivity, and its methyl carbonate prodrug24 with improved solubility in organic solvents. Furthermore, 14, was shown to reduce the proliferation of several liver cancer cells derived directly from patients.